Environmental and Urban Planning Aspects of the Introduction of Green Parking Lots in Tashkent - Abbos o’g’li, Axmedov Shaxobidinxon (Journal of Innovation in Education and Social Research, 2024)
This article is dedicated to the importance and necessity of designing green parking lots in the city of Tashkent. Green parking lots are environmentally sustainable and energy-efficient, helping to reduce the impact of the transportation system on the environment. The article discusses the existing issues in Tashkent's transportation infrastructure, the increasing air pollution, and the role of green parking lots in combating climate change. The article also provides practical recommendations for the construction of green parking lots in Tashkent.